SIKAP DAN KEPUASAN KONSUMEN TERHADAP KONSUMSI MAKANAN PECEL LELE DI KOTA BANDAR LAMPUNG - Deni Yuda Pratama; Yaktiworo Indriani; Teguh Endaryanto (Lampung University, 2017)
This study aimed to investigate the consumers’ characteristics, attitudes and satisfaction toward the attributes of “pecel lele” and the level of consumer’s satisfaction on the restaurant services. This research was conducted at two restaurants, namely MP Asli Hang Dihi and Ibu Safe'i, in Bandar Lampung City. The data was collected in January-March 2016 by a survey method and involving 60 respondents. The data of consumers’ attitudes was analyzed by Fishbein Multiatribute, whereas the level of consumers’ satisfaction was calculated by Customer Satisfaction Index (CSI). The result showed that consumers of both restaurants were 17-21 years old, most ot them were students of Bachelor (S1) and had monthly income or allowance from their parents ranging from Rp300,000 to Rp700,000 (at MP Asli Hang Dihi) and from Rp800,000 to Rp1,500,000 (at Ibu Safe'i). The score of consumers’ attitudes toward”pecel lele” at Ibu Safe'i was 40.9, while at MP Hang Dihi was 37.9. The level of consumer satisfaction index toward the restaurant services of Ibu Safe'i was 71.52 percent and of MP Hang Dihi was 70.50 percent. The highest score of among all attitudes and services were given to the taste. Key words: attitudes, consumer, pecel lele, satisfaction, taste